Gambaran Determinan Kejadian Stunting di Wilayah Kerja Puskesmas Wani: Determinants of Stunting in The Working Area Of Wani Healthy Centre - Sapriana; Hanum Sasmita (Media Publikasi Cendekia Indonesia, 2023)
Background: In Central Sulawesi, the percentage of short and very short toddlers is 20.4% and 11.9% respectively, higher than the national percentage of 19.3% and 11.5% (BPS Prop. Central Sulawesi, 2020). In the working area of ​​the Wani Health Center there were 198 stunting cases (UPTD Wani Health Center, 2020). Aims: to describe the determinants of stunting including maternal factors, child factors, family income and ownership of basic sanitation facilities in households with stunting cases. Methods: This research is a descriptive research. It will be held in April 2021. Data is collected by interviewing housewives and home observations. The number of samples is the total population, totaling 198 stunted children. The research instruments are in the form of questionnaires and questionnaires. Furthermore, the data were analyzed descriptively. Results: Of the 198 cases of stunting in the PKM Wani work area in 2021, 88.9% have a lower family income than the UMR of Central Sulawesi Province; 75.3% have family latrines that are not sanitary; 53% of children are male; 40.4% first child; 67.7% of mothers are housewives, with a median age of 30 years, the youngest being 18 years and the oldest being 48 years. Conclusion: Of the 198 cases of stunting, 88.9% had a family income lower than the UMR of Central Sulawesi Province; 75.3% have family latrines that are not sanitary (the distance of the septic tank from the water source is less than 10 meters); 53% are male; 40.4% first child; 67.7% of mothers are housewives, with a median age of 30 years. It is hoped that this will increase cross-sector collaboration, so that income, food availability, and community insights will improve, especially for households with cases of stunting under five.